Pengembangan Media Video Pembelajaran Pada Mata Kuliah Kalkulus Peubah Banyak - Arie Wahyuni; Destia Wahyu Hidayati (Jurnal Inovasi Pendidikan Matematika (JIPM), 2021)
This study aims to develop instructional video media in mathematics computer application program courses. This research is a Research and Development type of research with a 4D model, namely define, design, develop, and disseminate. From the results of this study it can be concluded that 1) the assessment obtained by the material expert on the instructional video media got a percentage score of 83% (very good), the assessment obtained by the media expert on the instructional video media got a percentage score of 87.5% (very good), 3) the response from students to instructional video media got a percentage score of 87.5% (very good).